Identification of Factors and Risk Assessments on Financial Literacy: A Case Study on Home Purchases - Sapiri, Hasimah (UUM Press, 2023)
Owning a house is among the significant aspects of a productive lifestyle. However, the persistent rise in house prices has affected homeownership for low-income young adults. Due to the poor financial literacy among employed young adults in Malaysia, it is more difficult for them to own a home due to financial constraints. Therefore, this study intends to investigate the factors contributing to financial literacy and the potential risk associated with its absence among working young adults. The methodologies used in this study were the factor analysis approach and decision tree analysis. Note that this study investigates financial literacy among young adults. A questionnaire was utilized for gathering the data, and a convenient sampling technique was adopted for data collection. According to the findings, four variables influence financial literacy among working youths: financial knowledge, financial behavior, financial education, and financial attitude. Consequently, the factors listed in exploratory data analysis in these four variables have been summarized to examine the perceived risk of financial literacy among adolescents in terms of purchasing a home. Finally, this study contributes as a guideline for policymakers in offering structured awareness programmes to improve financial literacy as well as homeownership knowledge among working youths for their future financial resilience.